An investigation into the tribology and corrosion barrier performance of thin multilayer PVD films - Daure, Jaimie (2016)
As surface engineering develops, the methods of applying coatings and the materials used have improved significantly. One method of coating deposition that is becoming increasingly popular is physical vapour deposition (PVD). This research investigates PVD coatings of single layered systems, dual layered systems and multilayered systems with varying layer thicknesses. The properties of the coatings are investigated along with the dependence of those properties on the coating materials, the coating architecture, the hardness and surface finish of the substrates used as well as the deposition conditions. Tests were carried out on the coatings to investigate their tribological and corrosion resistant properties compared against industry standard benchmark coatings of electrodeposited chromium and nickel respectively. The base materials chosen were as follows: CrN (hard wearing) and Graphit-iC (low friction) for the durable and low friction coatings; corrosion resistant IN625 and chromium for the scratch and corrosion resistant coatings. The results showed that multilayering can be an effective tool for increasing the hardness and scratch resistance of a coating system; however, no benefit was seen in terms of the wear and corrosion resistance of the selected coating systems through multilayering. In terms of corrosion behaviour of the coated systems, the coatings themselves were corrosion resistant, and therefore the system behaviour depends upon the barrier properties of the PVD films. PVD coatings contain growth defects which provide a route for exposure of the substrate to the corrosive media. Irrespective of the film architecture, the substrate surface finish was seen to play a significant role in determining defect density, resulting in a lower defect density for coatings deposited on substrates with a finer surface finish, which resulted in an improvement in the corrosion barrier properties of the resulting films.